A new approach to radon temporal correction factor based on active environmental monitoring devices - T. Dicu (Nature Portfolio, 2021)
Abstract The present study aims to identify novel means of increasing the accuracy of the estimated annual indoor radon concentration based on the application of temporal correction factors to short-term radon measurements. The necessity of accurate and more reliable temporal correction factors is in high demand, in the present age of speed. In this sense, radon measurements were continuously carried out, using a newly developed smart device accompanied by CR-39 detectors, for one full year, in 71 residential buildings located in 5 Romanian cities. The coefficient of variation for the temporal correction factors calculated for combinations between the start month and the duration of the measurement presented a low value (less than 10%) for measurements longer than 7 months, while a variability close to 20% can be reached by measurements of up to 4 months. Results obtained by generalized estimating equations indicate that average temporal correction factors are positively associated with CO2 ratio, as well as the interaction between this parameter and the month in which the measurement took place. The impact of the indoor-outdoor temperature differences was statistically insignificant. The obtained results could represent a reference point in the elaboration of new strategies for calculating the temporal correction factors and, consequently, the reduction of the uncertainties related to the estimation of the annual indoor radon concentration.